2007
DOI: 10.1128/aac.00628-07
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Efficacy of New Antifolates against Trimethoprim-Resistant Bacillus anthracis

Abstract: Bacillus anthracis is innately resistant to trimethoprim (TMP), a synthetic antifolate that selectively inhibits several bacterial dihydrofolate reductases (DHFRs) but not human DHFR. Previously, we were able to confirm that TMP resistance in B. anthracis (MIC > 2,048 g/ml) is due to the lack of selectivity of TMP for the B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…RAB1 inhibited growth of both Gram-negative (F. tularensis, Y. pestis, and B. abortus) and Gram-positive (B. anthracis, VRE, and S. aureus) organisms, indicating a broad-spectrum profile of activity (Table 3). Despite initial selection of RAB1 (previously BAL17662) for its inhibitory activity against B. anthracis, the present results demonstrate a potent antistaphylococcal profile (3). Among the organisms tested, F. tularensis, B. abortus, B. anthracis, VRS1, and VRS2 have an MIC for TMP of Ն16 g/ml, which is classified as resistant by CLSI (11).…”
Section: Resultsmentioning
confidence: 81%
“…RAB1 inhibited growth of both Gram-negative (F. tularensis, Y. pestis, and B. abortus) and Gram-positive (B. anthracis, VRE, and S. aureus) organisms, indicating a broad-spectrum profile of activity (Table 3). Despite initial selection of RAB1 (previously BAL17662) for its inhibitory activity against B. anthracis, the present results demonstrate a potent antistaphylococcal profile (3). Among the organisms tested, F. tularensis, B. abortus, B. anthracis, VRS1, and VRS2 have an MIC for TMP of Ն16 g/ml, which is classified as resistant by CLSI (11).…”
Section: Resultsmentioning
confidence: 81%
“…Previous studies revealed a high selectivity of RAB1 for B. anthracis DHFR over human DHFR (IC 50 ϭ 54 nM versus 110,000 nM) (7). A comparison of binding sites was made using the human DHFR structure complexed with MTX and NADPH (PDB ID code 1U72, RMS deviation ϭ 2.05 Å) (20).…”
Section: Structure Of B Anthracis Dhfr-rab1 Complexmentioning
confidence: 99%
“…We have previously identified dihydrophthalazine TMP derivative inhibitors for this target (7). Variation of the moiety attached to the dihydrophthalazine ring produced 50% inhibitory concentrations (IC 50 s) ranging from 46 to 600 nM (6).…”
mentioning
confidence: 99%
“…Based on previous work by Basilea Pharmaceutica 11-14 and Barrow et al, 4 a number of DAP inhibitors were designed, synthesized, and evaluated for their biological activities. The initial modifications were made at R 1 on the dihydrophthalazine ring.…”
Section: Introductionmentioning
confidence: 99%